2010
DOI: 10.3148/71.4.2010.186
|View full text |Cite
|
Sign up to set email alerts
|

Healthier Snacks in School Vending Machines: A Pilot Project in Four Ontario High Schools

Abstract: Replacing 50% of vending stock with healthier snacks resulted in a decline in vending revenues. Future health programs in schools need to provide "real" healthy snacks, such as low-fat dairy products, fruits, and vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 6 publications
2
35
0
1
Order By: Relevance
“…7 Several North American school districts have developed vending machine policies that have been implemented at the elementary and secondary school level. [8][9][10][11][12] Policies ranged from turning off machines during the lunch period 8 or limiting accessibility to vending machines, 9,10,12 decreasing the availability of unhealthy foods, increasing availability of healthier foods, 8 and ensuring foods meet specific nutritional standards. 12 Few college campuses have nutrition policies regarding healthy vending.…”
Section: Brief Reportmentioning
confidence: 99%
“…7 Several North American school districts have developed vending machine policies that have been implemented at the elementary and secondary school level. [8][9][10][11][12] Policies ranged from turning off machines during the lunch period 8 or limiting accessibility to vending machines, 9,10,12 decreasing the availability of unhealthy foods, increasing availability of healthier foods, 8 and ensuring foods meet specific nutritional standards. 12 Few college campuses have nutrition policies regarding healthy vending.…”
Section: Brief Reportmentioning
confidence: 99%
“…19 While a number of studies across Canada have examined the success of school nutrition policy implementation, as measured by the availability of healthy foods in cafeterias and tuck shops (i.e., school stores), few have evaluated the extent to which school vending machines, specifically, are policy compliant. 20,21 Further, research on implementation in the secondary school environment (grades 9-12) has been limited, and virtually absent from evaluations of vending machine contents in Ontario. Given the challenges associated with evaluating province-wide healthy eating and physical activity policies in schools (i.e., based on variability in policy components, policy implementation), Ramanathan et al 22 highlight the value in matching Ontario public schools with out-of-province schools for indicators of overall policy effectivesness, and treatmentcontrol comparisons.…”
Section: School Interventions To Promote Healthy Eatingmentioning
confidence: 99%
“…Studies that investigated the impact of school food policies within Canada and the United States have generally resulted in some positive outcomes, such as improved eating habits (e.g., Bevans, Sanchez, Teneralli, & Forrest, 2011;Cullen, Watson, & Zakeri, 2008;Mullally et al, 2010) and increased knowledge, attitudes, and willingness to try new foods (Day, Naylor, & McKay, 2009); however, research showed that insufficient communication, lack of facilities and staff, lack of appealing food choices, cost (e.g., 'good for value'), and portion sizes of these healthier choices were barriers to implementing these policies (Callaghan, Mandich, & He, 2010;MacLellan et al, 2010;Rushowy, 2012). In addition, exceptions to the policies such as allowing staff, public, and other programs to continue purchasing food with minimal nutritional value or bring in food from home, were likely to reduce the overall effect of the policy in achieving its goals (Whatley-Blum et al, 2011).…”
Section: Empirical Evaluation Of School Food Policiesmentioning
confidence: 99%